(untitled) (Journal of the College of Education for Women, 2022)
This study aims to explore the relationship between the degree of application of digital leadership and the development of administrative work at the University of Tabuk. It further aims to examine the presence of statistically significant differences between the average responses of faculty members and employees at the University of Tabuk regarding the study axes that are attributed to the following variables: (scientific rank, gender, and job), the study used the descriptive approach in its correlative style, and the questionnaire was used as a tool for data collection, as it was applied to a simple random of (310) members of the faculty and staff. University of Tabuk. The results showed that the degree of digital leadership application at the University of Tabuk is medium, and that the degree of approval of the reality of administrative work at the University of Tabuk is medium. A statistic between the response averages of the study sample members according to the degree variable (assistant professor, associate professor, and professor) in the axes of digital leadership and administrative work at the significance level of 0.05 and 0.01. In favor of an assistant professor, as well as the presence of statistically significant differences in the gender variable for the axes of the study, digital leadership and the development of administrative work, and the absence of statistically significant differences between the responses of the study sample members according to the job variable, for the axes of the study, digital leadership, and the development of administrative work.